Autoimmune Encephalitis and Other Neurological Syndromes With Rare Neuronal Surface Antibodies in Children: A Systematic Literature Review - Ancona, Claudio; Masenello, Valentina; Tinnirello, Matteo; Toscano, Luca Mattia; Leo, Andrea; La Piana, Chiara; Toldo, Irene; Nosadini, Margherita; Sartori, Stefano (Frontiers in Pediatrics, 2022)
Neuronal surface antibody syndromes (NSAS) are an expanding group of autoimmune neurological diseases, whose most frequent clinical manifestation is autoimmune encephalitis (AE). Anti-NMDAR, anti-LGI1 and anti-CASPR2 autoimmunity represent the most described forms, while other NSAS are rarer and less well characterised, especially in children. We carried out a systematic literature review of children with rare NSAS (with antibodies targeting D2R, GABAAR, GlyR, GABABR, AMPAR, amphiphysin, mGluR5, mGluR1, DPPX, IgLON5, neurexin-3alpha) and available individual data, to contribute to improve their clinical characterisation and identification of age-specific features. 94 children were included in the review (47/94 female, age range 0.2-18 years). The most frequent NSAS were anti-D2R (28/94, 30%), anti-GABAAR (23/94, 24%), and anti-GlyR (22/94, 23%) autoimmunity. The most frequent clinical syndromes were AE, including limbic and basal ganglia encephalitis (57/94, 61%) (GABAAR, D2R, GABABR, AMPAR, amphiphysin, mGluR5), and isolated epileptic syndromes (15/94, 16%) (GlyR, GABAAR). With the limitations imposed by the low number of cases, the main distinctive features of our paediatric literature cohort compared to the respective NSAS in adults included: absent/lower tumour association (exception made for anti-mGluR5 autoimmunity, and most evident in anti-amphiphysin autoimmunity); loss of female preponderance (AMPAR); relatively frequent association with preceding viral encephalitis (GABAAR, D2R). Moreover, while SPS and PERM are the most frequent syndromes in adult anti-GlyR and anti-amphiphysin autoimmunity, in children isolated epileptic syndromes and limbic encephalitis appear predominant, respectively. To our knowledge, this is the first systematic review on rare paediatric NSAS. An improved characterisation may aid their recognition in children.